Drop height is influenced by box height but not by individual stature during drop jumps (Journal of Physical Education (Maringá), 2019)
Drop jump (DJ) performance an important aspect in many sports. The optimal stretch load in the DJ training is commonly prescribed through the box height from which individuals must drop from. However, studies have reported differences between real (calculated) drop heights and box heights, which may affect the quality of the prescription of DJ training load. Other aspects such as individual stature may also affect the differences between calculated drop heights and box heights. This study aimed to 1) investigate the difference between calculated drop heights and box heights in different box heights and 2) verify the influence of individual stature on the difference between calculated drop heights and box heights. Twenty-two male physical education students performed DJs from different box heights (i.e., 20, 30, 40, and 50 cm) and landed on a force platform. The drop height was calculated by the impulse-momentum method. An ANCOVA covariance analysis was performed to verify the influence of stature and box height on the difference between calculated drop heights and box heights. We found that calculated drop height was different from box height for all box heigths. The difference between calculated drop height and box height significantly increased as box heights increased. Individual stature did not influence the difference between calculated drop heights and box heights. We can concluded that box heights are significantly different from calculated drop heights. These differences increase as the box height increases, i.e. an increase in the difference of approximately 2 cm every 10 cm increase in box height. Apparently, individual stature does not affect the difference between calculated drop heights and box height. Therefore, it seems that coaches can use the same procedures for prescribing DJ training load for individuals of different heights.